PENGARUH TOTAL QUALITY MANAGEMENT, SISTEM PENGUKURAN KINERJA, SISTEM PENGHARGAAN TERHADAP KINERJA MANAJERIAL (Studi Empiris Pada Perusahaan Asuransi DI Pekanbaru) - Zul Azmi; Andreas -; Enni Savitri (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Ekonomi, 2015)
The Purpose of this study was to gain empirical evidence referred to the effect of Total Quality Management, performance measurement system, the reward system to managerial performance in the insurance companies in Pekanbaru. The Population of this study was all managers in the insurance company in Pekanbaru. The number of respondents who used as samples were 43 managers of the insurance companies. The data analysis method was multiple regression analysis. The result of the study shows that there were the direct effect of Total Quality Management to managerial performance. While, both of the performance measurement system and reward systems have no effect to managerial performance.Keywords: Total Quality Management, performance measurement system, reward system, and managerial performance